A New MRI-Defined Biomarker for Rectal Mucinous Adenocarcinoma: Mucin Pool Patterns in Determining the Efficacy of Neoadjuvant Therapy - Cao, Wuteng; Wu, Lei; Zhao, Yandong; Zhou, Jie; Li, Wenli; Wang, Xinhua; Xu, Jianbo; Zhou, Zhiyang; Liang, Changhong (Frontiers in Oncology, 2020)
Background and aim: To study the relationship between MRI-defined mucin pool (MP) patterns prior to treatment and the efficacy of neoadjuvant therapy (NAT) in locally advanced rectal mucinous adenocarcinoma (RMAC). Methods: This retrospective study included 278 RMAC patients evaluated between January 2012 and January 2019. After trained by using 118 cases with postoperative pathological images, radiologists distinguished MRI-defined MP status as mixed type (MTMP) and separate type (STMP) in NAT cohort (160 patients) in addition to tumor characteristics, invasion of mesorectal facia and nodal status. Reader reproducibility was determined using the κ coefficient. The main outcome was the accuracy of MP dichotomy in predicting whether patients had tumor responsiveness or not. Results: Among 278 cases, MTMP and STMP accounted for 49.6% and 50.4% of MPs, respectively. 72 patients received neoadjuvant chemoradiotherapy and 88 received chemotherapy. The tumor responsiveness rate in the chemoradiotherapy group was higher than that in the chemotherapy group (58.3% vs. 21.6%, P < 0.001). In the chemotherapy group, the tumor responsiveness rate in patients with MTMPs was lower than that in patients with STMPs (4.9% vs.25.5%, P = 0.002). The baseline MRI-defined MTMP was associated with lower responsiveness rates after NAT in the chemotherapy group (odds ratio, 11.050, with 95%CI, 2.368~51.571, P = 0.002). Conclusions: MP dichotomy can be reliably evaluated by using MRI. In the chemotherapy group, MTMP may be a dependent predictor to indicate a lower likelihood of tumor responsiveness after NAT.